Dispositivo y aplicación informativa para disminuir el contagio de ets e its para prácticas sexuales entre personas con vulva - Lopez Prada, Karen Elizabeth; Marin Puerto, Laura Juliana (Universidad Antonio Nariño, 2022)
In this project, it was carried out the design of a device for diminishing the sexual transmission diseases in which it is focused towards people with vulva since 61% (Silberman, P., Buedo, P.E.. & Burgos, L. M. (2016)) of these would not have a prior knowledge from the risk of infection when there exist sexual practices in between; some of the deseases that can get transmited through sex are: clamidia, clamidiasis, gonorrea, sifilis, condilomas, viral hepatatis, genital herpes, HIV, etc. On the other hand, within the current trade such as pharmacies and store’s franchises, there are prevention device’s distribution exclusively for approaches that include any kind of penetration linked towards men. Covering the subject, the sexual practice along people with vulva yet is seen as a tabu and this generates that the device’s comercial trade such as: latex barrier, tongue’s cover devices and finger’s condoms are only sold in shops like sex shops, being this products not providing any kind of safe protection. Those mentioned devices are not versatile for a diversity of sexual practices such as: cunnilingus, tribadism, masturbation, vaginal penetration and erotic massages.